ANALISIS ABNORMAL RETURN SEBELUM DAN SESUDAH PELARANGAN EKSPOR BATU BARA PADA 1 JANUARI 2022 - Darmawati, Darmawati; Rasyid, Syarifuddin; Amalia, Lestari Rezki Nurul; Nurazisah, Andi Fadhilah (Universitas Nusa Cendana, 2024)
This study aims to analyze the difference in average abnormal stock returns before and after the announcement of the coal export ban on coal mining companies on the Indonesia Stock Exchange (IDX) between August 2021 and January 2022. The method used is an event study with secondary data from Yahoo Finance. The research sample consisted of 20 companies. The analysis used the Shapiro-Wilk normality test, the one-sample Sample T-Test test for normal data, and the Wilcoxon Signed Rank Test for abnormal data. The results showed a significant abnormal return on the days surrounding the announcement of the export ban, but there was no significant difference between the abnormal return before and after the announcement. The limitations of this study are the limited sample and short analysis period. Suggestions for future research are to expand the sample and period and consider external factors that affect abnormal returns. Keywords: Abnormal Return; Export Ban; IDX Shares